Student Perceptions of the Use of Authentic Video in Learning Arabic Writing Skills - Muhammad Nur Kholis; Muhammad Zaenuri; Syaifullah Syaifullah; Rumpoko Setyo Jatmiko (Jurusan Pendidikan Bahasa Arab UIN Kiai Ageng Muhammad Besari onorogo, 2025)
Authentic video is one of the media that can be used in the process of learning to write Arabic because it has many benefits such as providing a real picture of the use of language in life and cultural insights, improving students' language learning experience, and stimulating student interest and involvement in the learning process. This study aims to explain students' perceptions of the use of authentic videos in learning to write Arabic. This research used quantitative design and was conducted on 34 students of Arabic Language and Literature UIN Raden Mas Said Surakarta. Students who have finished the Arabic writing course are asked to fill out a questionnaire through Google Form. The collected data is then analyzed using descriptive statistics, namely averages and standard deviations. The results of this study show that students have a positive perspective on the use of authentic videos in learning to write Arabic. Authentic videos are considered to provide contextual and imaginative depictions of real-life objects and situations and can inspire students to be more involved in learning languages. Therefore, it can increase demand and motivation in learning to write Arabic. This study recommends that Arabic practitioners include authentic videos as one of the media and learning resources in the process of learning Arabic writing in particular and Arabic learning in general. Abstrak Video autentik merupakan salah satu media yang dapat digunakan dalam proses pembelajaran menulis bahasa Arab karena mempunyai banyak manfaat seperti memberikan gambaran yang nyata mengenai penggunaan bahasa dalam kehidupan dan wawasan budaya, meningkatkan pengalaman belajar bahasa siswa dan merangsang minat dan keterlibatan siswa dalam proses pembelajaran. Penelitian ini bertujuan untuk menjelaskan bagaimana persepsi mahasiswa terhadap penggunaan video autentik dalam pembelajaran menulis bahasa Arab. Penelitian ini menggunakan desain kuantitatif dan dilakukan pada 34 mahasiswa jurusan Bahasa dan Sastra Arab UIN Raden Mas Said Surakarta. Mahasiswa yang sudah selesai mengikuti mata kuliah menulis bahasa Arab diminta untuk mengisi kuesioner melalui Google Form. Data yang terkumpul kemudian dianalisis menggunakan statistik deskriptif yaitu menggunakan rata-rata dan standar deviasi. Hasil penelitian ini menunjukkan bahwa mahasiswa mempunyai perspektif positif terhadap penggunaan video autentik dalam pembelajaran menulis bahasa Arab. Video autentik dianggap dapat memberikan gambaran objek dan situasi kehidupan nyata yang kontekstual dan imajinatif, serta dapat menginspirasi siswa untuk lebih terlibat dalam belajar bahasa. Maka dari itu, dapat meningkatkan minat dan motivasi dalam belajar menulis bahasa Arab. Penelitian ini merekomendasikan agar para praktisi bahasa Arab memasukkan video autentik sebagai salah media dan sumber belajar dalam proses pembelajaran menulis bahasa Arab pada khususnya dan pembelajaran bahasa Arab pada umumnya.